Pengaruh Tontonan Upin & Ipin Terhadap Pemerolehan Bahasa Pada Usia 8 Tahun - Putri Nirma Lailiyani; Irwan Suswandi (Lingua: Jurnal Bahasa, Sastra dan Pengajarannya)
The Malay-language Upin & Ipin animated series is very popular with children. However, watching Upin & Ipin too often can have a negative influence on children’s language development. According to psycholinguistic, it can be related to language acquisition in children especially in early childhood which is in the critical stage of first language acquisition. The purpose of this study is to analyze an 8-year-old boy with the initial N who lives in Ungaran village. The child has language differences in communication. The theory in this study uses behaviorism according to Watson (1998). The research method used is the simak method with basic technique, i.e. sadap technique; then the advanced technique used are the simak bebas libat cakap (SBLC) technique and rekam technique. The results found 10 conversational data using Malay language as a response to the boy with the initial N in communicating and 6 non-conversational data in the form of vocabulary used by the boy.